Sustainable Waste Management Practices in Indonesia - Burhanuddin, Burhanuddin (Sinergi International Journal of Management and Business, 2024)
This study explores how social capital, community empowerment, and social entrepreneurship efforts impact sustainable waste management practices in Indonesia. A numerical method was used to survey 238 different villages in various areas. Key features, such as where the samples were located, how many people were involved, and their social and economic backgrounds, were thoroughly examined. Descriptive statistics, evaluation of the measurement model, and analysis of the structural model were conducted to understand the complex connections between the variables under investigation. The results show important and beneficial connections between social capital, community empowerment, social entrepreneurship projects, and waste management techniques. The model fit assessment attests to the validity of the proposed relationships. In addition, an obvious implication of this research is the increased awareness of each party be it the community, government and social enterprises. Community engagement through the level of social capital has been recognised in this study followed by statistical evidence, as well as community empowerment and social entrepreneurship. Effective waste management is generated by collaboration between all elements.